Ukraïnica : the primary database of ukrainian sources - Harvard Ukrainian Research Institute (2019)
A database of primary and secondary sources that are recommended by practitioners in the field of Ukrainian studies, equipped with six levels of taxonomy to allow for searching by tropes, periods, decades, genres, disciplines and authors or directors, the originators of the source in question